GENETICS AND MOLECULAR ASPECTS OF PROSTATE CANCER: REVIEW - SANDEEP SINGH (International Journal of Pharma and Bio Sciences, 2014)
Inspite of progress in diagnosis, treatment prostate cancer has become one of the most frequent lethal cancers in males. Rate of detection of prostate cancer varies widely across the world. Research on molecular biology of prostate cancer is expected to give new insight of improving, distinguishing slow growing from aggressive clinically relevant cancers and provide target for treatment. Traditionally, prostate cancer research focused on prostate structure, development and hereditary aspects. This review mainly focuses on novel finding of genetics and molecular biological aspects of the prostate cancer like alteration of androgen signaling, investigation of the tumor suppressor gene, proto Oncogenes and studies of chromosomal alteration followed by telomerase activity